The Use of AI In Legal Case Analysis and Court Outcome Prediction: Opportunities, Challenges and Ethical Implications - Didy Hermawan; Burham Pranawa (Journal of Law, Society and Living Norms, 2025)
This study investigates Artificial Intelligence (AI) applications in legal case analysis and court outcome prediction within Indonesia's judicial system. Using qualitative descriptive analysis through comprehensive literature review of journal articles, books, and legal documents, this research examines opportunities, challenges, and ethical implications of AI implementation in legal practice. Findings reveal AI's significant potential for enhancing judicial efficiency through task automation, improving accuracy via pattern recognition and data analysis, and increasing accessibility through digital legal services. However, critical challenges include algorithmic bias perpetuating systemic inequalities, transparency deficits in decision-making processes, accountability gaps in AI recommendations, and data protection concerns under Indonesia's Personal Data Protection Law. Ethical implications encompass fairness issues in justice delivery, potential reduction of human oversight, privacy risks from data collection, and social impacts on legal profession dynamics. This research provides original insights through comprehensive analysis tailored to Indonesian legal framework, integrating Justice Theory, Computational Ethics, Legal Subject Theory, and Regulatory Theory. The study concludes that responsible AI integration requires developing regulatory frameworks, enhancing transparency mechanisms, addressing algorithmic bias, protecting personal data, maintaining human oversight, and promoting stakeholder collaboration to ensure ethical AI deployment in Indonesia's judicial system.